PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS LAPORAN SISWA KELAS VIII SMP - Ary Kristiyani (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aimed to describe the improvement of the quality of the report writing learning process and the improvement of students’ report writing skills through the contextual approach. This study was an action research study employing John Elliott’s model consisting of two cycles. The subjects were Year VIII E studentsof SMP Negeri 1 Juwana. The data were collected through tests, observations, field notes, and interviews and were analyzed by means of the qualitative and quantitative descriptive techniques. The results showed that: (1) the learning of report writing was better than that conducted before; (2) students’ writing skills at the end of Cycle II (9.03) were better (mean = 9.03) than those before the action (mean = 7.71). Therefore, it was concluded that the application of CTL was capable of improving the quality of the report writing learning and the report writing skills of Year VIII Estudents of SMP Negeri 1 Juwana.